Flying under the radar – impact and factors influencing asymptomatic DENV infections - Henriques, Paulo; Rosa, Alexandra; Caldeira-Araújo, Helena; Soares, Pedro; Vigário, Ana Margarida (Frontiers in Cellular and Infection Microbiology, 2023)
The clinical outcome of DENV and other Flaviviruses infections represents a spectrum of severity that ranges from mild manifestations to severe disease, which can ultimately lead to death. Nonetheless, most of these infections result in an asymptomatic outcome that may play an important role in the persistent circulation of these viruses. Also, although little is known about the mechanisms that lead to these asymptomatic infections, they are likely the result of a complex interplay between viral and host factors. Specific characteristics of the infecting viral strain, such as its replicating efficiency, coupled with host factors, like gene expression of key molecules involved in the immune response or in the protection against disease, are among crucial factors to study. This review revisits recent data on factors that may contribute to the asymptomatic outcome of the world's widespread DENV, highlighting the importance of silent infections in the transmission of this pathogen and the immune status of the host.